PENINGKATAN KREATIVITAS SISWA PADA PEMBELAJARAN PRAKARYA DI KELAS VIII A SMPN 03 PADANG PANJANG - Putri Ramayani; Amrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the development of students’ creativity in craft learning through the utilization of paper waste as a learning medium. Creativity plays an essential role in education as it encourages students to think innovatively, participate actively, and produce meaningful works. However, students’ creativity is often not optimally developed, requiring contextual and experience-based learning approaches. This study aims to describe the learning process and analyze the improvement of students’ creativity through paper waste utilization in Prakarya (craft) learning. A descriptive qualitative method was employed, involving 27 students of class VIII A at SMP Negeri 03 Padang Panjang. Data were collected through observation, interviews, and documentation, and analyzed using descriptive techniques with triangulation to ensure validity. The findings indicate that the use of paper waste enhances students’ creativity, as reflected in their increased participation, confidence in expressing ideas, and ability to produce varied creative works. In addition, hands-on activities and collaborative learning foster students’ innovative thinking and problem-solving skills. In conclusion, the utilization of paper waste as a learning medium positively contributes to improving students’ creativity and supports more innovative and contextual learning practices.